X-ray diffraction analysis of MTA mixed and placed with various techniques - BAŞTÜRK, FATIMA BETÜL; GÜNDAY, MAHİR (SPRINGER HEIDELBERG, 2018)
Objectives The aim of this study was to evaluate the effect of various mixing techniques as well as the effect of ultrasonic placement on hydration of mineral trioxide aggregate (MTA) using X-ray diffraction (XRD) analysis. Materials and methods One gram of ProRoot MTA and MTA Angelus powder was mixed with a 0.34-g of distilled water. Specimens were mixed either by mechanical mixing of capsules for 30 s at 4500 rpm or by manual mixing followed by application of a compaction pressure of 3.22 MPa for 1 min. The mixtures were transferred into the XRD sample holder with minimum pressure. Indirect ultrasonic activation was applied to half of the specimens. All specimens were incubated at 37 degrees C and 100% humidity for 4 days. Samples were analyzed by XRD. Phase identification was accomplished by use of search-match software utilizing International Centre for Diffraction Data (ICDD). Results All specimens comprised tricalcium silicate, calcium carbonate, and bismuth oxide. A calcium hydroxide phase was formed in all ProRoot specimens whereas among MTA Angelus groups, it was found only in the sample mixed mechanically and placed by ultrasonication. Conclusions Mechanical mixing followed by ultrasonication did not confer a significant disadvantage in terms of hydration characteristics of MTA.
Keywords: Calciumhydroxide; MTA; Mechanical mixing; Ultrasonic agitation; X-ray diffraction analysis; XRD; MINERAL TRIOXIDE AGGREGATE; WHITE PROROOT MTA; PORTLAND-CEMENT; COMPRESSIVE STRENGTH; CHEMICAL-ANALYSIS; MIXING TECHNIQUES; BISMUTH OXIDE; PARTICLE-SIZE; HYDRATION; SOLUBILITY